Synthesis of Well-Defined Three-Arm Star-Branched Polystyrene through Arm-First Coupling Approach by Atom Transfer Radical Polymerization - Syed Shahabuddin; Fatem Hamime Ismail; Sharifah Mohamad; Norazilawati Muhamad Sarih (International Journal of Polymer Science)
Here we describe a simple route to synthesize three-arm star-branched polystyrene. Atom transfer radical polymerization technique has been utilized to yield branched polystyrene involving Williamson coupling strategy. Initially a linear polymeric chain of predetermined molecular weight has been synthesized which is further end-functionalized into a primary alkyl bromide moiety, a prime requisition for Williamson reaction. The end-functionalized polymer is then coupled using 1,1,1-tris(4-hydroxyphenyl)ethane, a trifunctional core molecule, to give well-defined triple-arm star-branched polystyrene.